Enhancing sintering of kaolinitic clay from DRC using cassava waste ash: A novel aid for optimizing ceramic performance - Aboubakar Moustapha; Youssef Arkame; Ayoub Imgirne; Ahmed Manni; Tarik Tamri; Achraf Harrati; Fahd Oudrhiri Hassani; Laila Laasri; Chaouki Sadik (Next Materials, 2025)
This study investigates the effects of incorporating cassava peel ash into ceramics at different sintering temperatures, aiming to optimize conditions for improved energy efficiency and offering an innovative approach that addresses both waste management and sustainable ceramic processing. First, the raw materials' thermal behavior by TDA-TGA, and chemical and mineralogical composition were determined by processing XRF and XRD techniques. The existence of Kaolinite was confirmed in the clay sample, while alkaline elements revealed by XRF analysis were found in the ash of cassava peel (ACP). Ceramics containing 0, 2.5, 5, and 7.5 wt% of ACP were successfully sintered at 1000, 1100, and 1200 °C. The morphological and ductile characteristics were recorded. Mechanical properties (flexural strength), technological properties (apparent porosity, apparent density, linear shrinkage, and water absorption), and chemical resistance to acidic and alkaline conditions were assessed. Mechanical strengths of 2.3, 7.8, and 16.5 MPa were obtained for ceramics sintered at 1000, 1100, and 1200 °C, depending on the inclusion of 7.5 wt% ACP. Although ACP improved ceramic sintering conditions, shrinkage ranged between 0.1 % at 1000 °C and 8.3 % at 1200 °C, hence 1100 °C with 2.1 % shrinkage was regarded as the optimal sintering condition with good consensus about temperature, shrinkage, and technological properties.